Things of Darkness : Economies of Race and Gender in Early Modern England - Hall, Kim F., 1961- (Book collections on Project MUSE., 1995)
The "Ethiope," the "tawny Tartar," the "woman blackamoore," and "knotty Africanisms"--Allusions to blackness abound in Renaissance texts. Kim F. Hall's eagerly awaited book is the first to view these evocations of blackness in the contexts of sexual politics, imperialism, and slavery in early modern England. Her work reveals the vital link between England's expansion into realms of difference and otherness-through exploration and colonialism-and the highly charged ideas of race and gender which emerged. How, Hall asks, did new connections between race and gender figure in Renaissance ideas about the proper roles of men and women? What effect did real racial and cultural difference have on the literary portrayal of blackness? And how did the interrelationship of tropes of race and gender contribute to a modern conception of individual identity? Hall mines a wealth of sources for answers to these questions: travel literature from Sir John Mandeville's Travels to Leo Africanus's History and Description of Africa; lyric poetry and plays, from Shakespeare's Antony and Cleopatra and The Tempest to Ben Jonson's Masque of Blackness; works by Emilia Lanyer, Philip Sidney, John Webster, and Lady Mary Wroth; and the visual and decorative arts. Concentrating on the sixteenth and seventeenth centuries, Hall shows how race, sexuality, economics, and nationalism contributed to the formation of a modern (white, male) identity in English culture. The volume includes a useful appendix of not readily accessible Renaissance poems on blackness